Zebrafish xenografts in breast cancer research - Rong, Xingyan; Chen, Han; Guo, Xiyuan; Sun, Xiaoke; Li, Lin; Ye, Yingchun; Li, Chenwen; Nian, Siji; Liang, Chengbi; Yuan, Qing (Frontiers in Immunology, 2025)
Breast cancer (BC) tops the list of all malignancies diagnosed in women worldwide, with many patients diagnosed only at the metastatic stage. Current therapeutic paradigms integrating early detection modalities and multimodal treatment strategies have improved outcomes, yet persistent challenges in managing advanced/metastatic cases result in suboptimal 5-year survival rates. Therefore, it is imperative to develop novel therapeutic strategies for BC. Zebrafish breast cancer models have received great attention in this regard, and this review highlights recent advances in BC research involving these zebrafish models. In vivo research using zebrafish models is becoming increasingly valuable for studying BC invasion and metastasis, tumor angiogenesis, and screening for novel therapeutic molecules. These studies have provided insights into the molecular mechanisms of BC, potential drug targets and their efficacy and toxicity, and the application of zebrafish in personalized medicine research. Against this background, this review provides a systematic analysis of the recent advances in zebrafish BC model research regarding brain metastasis, bone metastasis, tumor angiogenesis, and drug screening. The review also critically evaluates the strengths and limitations of the zebrafish model organism, while delineating the future research directions in this field.